Evaluation of the involvement of HIV positive patients in the decision to commence antiretroviral therapy at Oshakati Hospital, Namibia - Mavhunga, Farai (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPhil (Industrial Psychology))--University of Stellenbosch, 2009.